Efficacy of district tuberculosis co-ordinating team on health service performance for suspected TB patient in district hospital - Sasithorn Tangsawad; Surasak Taneepanichskul (College of Public Health Sciences, Chulalongkorn University, 2018)
Purpose - The purpose of this paper is to study the efficacy of a district tuberculosis (TB) co-ordinating team on health service performance for suspected TB patients in a district hospital in northeastern Thailand. Design/methodology/approach - A comparison study of pre- and post-evaluations of TB system improvement was conducted in a district hospital in northeastern Thailand between October 2016 and June 2017. Data collection reviewed the record of suspected TB cases reported in the district hospital in the past nine months as a base line for describing the health service performance in term of received investigation for TB diagnosis. Participants from a TB clinic, district health office and health center set up a TB co-ordinating team to explore situations and systematic gaps. The TB co-ordinating team gave recommendations of health service performance for suspected TB patients over a nine-month period. Records of suspected TB cases health service performance were collected nine months after intervention. Data analysis by descriptive statistics and to test the effect of intervention was performed. Findings - The records from 324 and 379 suspected TB cases reported in the hospital from the 9 months preceding and 9 months, respectively, after intervention were reviewed. A TB co-ordinating team was set up to improve the system and health service performance in terms of investigation for TB diagnosis. The results revealed that health service performance in terms of complete microscopy and investigation in both chest radiography and microscopy increased after intervention. When comparing between pre- and post-intervention, suspected cases received both chest radiography and microscopy in 176 cases and 283 cases, respectively (p-value=0.001). There were 27 cases diagnosed for smear positive TB in pre-intervention and 51 cases diagnosed in post-intervention (p-value=0.011). There were 21 cases pre- and 36 cases post-intervention that had referral documents from health center with no statistically significant difference. Originality/value - The TB co-ordinating team had the role to improve health service performance for suspected TB cases to enroll in investigation process for increase TB diagnosis in district hospital.